2018
DOI: 10.11591/ijeecs.v10.i1.pp138-145
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Addiction Detection based on Neurophysiological Computational Approach

Abstract: <span lang="EN">The rise of Internet access, social media and availability of smart phones intensify the epidemic of pornography addiction especially among younger teenagers. Such scenario may offer many side effects to the individual such as alteration of the behavior, changes in moral value and rejection to normal community convention. Hence, it is imperative to detect pornography addiction as early as possible. In this paper, a method of using brain signal from frontal area captured using EEG is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
1
10
0
2
Order By: Relevance
“…Based on the experimental result for both positive and negative emotion, Subject A and B yielded u pattern. Therefore, it can be concluded that children with ASD shows the consistency lower alpha power as supported by previous studies on the reducing of alpha power for ASD cases [5,10].…”
Section: Autism Spectrum Disordersupporting
confidence: 76%
See 1 more Smart Citation
“…Based on the experimental result for both positive and negative emotion, Subject A and B yielded u pattern. Therefore, it can be concluded that children with ASD shows the consistency lower alpha power as supported by previous studies on the reducing of alpha power for ASD cases [5,10].…”
Section: Autism Spectrum Disordersupporting
confidence: 76%
“…The frequencies implemented in this research study are delta (1-3Hz), theta (4-8Hz), alpha (9-13Hz), beta (14-25Hz) and also gamma (26Hz-40Hz). The processed EEG data were then used to extract features based on the Mel Frequency Cepstral Coefficients (MFCCs) technique which has been applied in several studies for brain signals analysis [8][9][10]. After features were extracted, at each instance target was labelled based on the emotions data used indicating positive emotion calm with labelled (1, -1) and for negative emotion (fear) with labelled (-1, 1) for valence and arousal (V, A) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such scenario can pose as a challenge especially if parents have the tendency to suppress their children situation [15]. There has been studies to analyse porn addiction using the brain wave patterns [16,17]. However, such study only considers the power distribution of the frontal areas during the eyes open and eyes close and comparison with learning disabilities [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data collection was prepared by the International Islamic University Malaysia (IIUM) researchers using the electroencephalogram (EEG) device for 14 Indonesian teenagers [17]. There are a total of 14 participants with age ranging between 9 to 13 years old EEG data was collected but only 11 participants data were used in this study.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation